Increased β‐haemolytic group A streptococcal M6 serotype and streptodornase B‐specific cellular immune responses in Swedish narcolepsy cases. (22nd March 2015) - Ambati, A.; Poiret, T.; Svahn, B.‐M.; Valentini, D.; Khademi, M.; Kockum, I.; Lima, I.; Arnheim‐Dahlström, L.; Lamb, F.; Fink, K.; Meng, Q.; Kumar, A.; et al.
Abstract Background Type 1 narcolepsy is a neurological disorder characterized by excessive daytime sleepiness and cataplexy associated with the HLA allele DQB1*06:02. Genetic predisposition along with external triggering factors may drive autoimmune responses, ultimately leading to the selective loss of hypocretin‐positive neurons. Objective The aim of this study was to investigate potential aetiological factors in Swedish cases of postvaccination (Pandemrix) narcolepsy defined by interferon‐gamma (IFNγ) production from immune cells in response to molecularly defined targets. Methods Cellular reactivity defined by IFNγ production was examined in blood from 38 (HLA‐DQB1*06:02+) Pandemrix‐vaccinated narcolepsy cases and 76 (23 HLA‐DQB1*06:02+ and 53 HLA‐DQB1*06:02−) control subjects, matched for age, sex and exposure, using a variety of different antigens: β‐haemolytic group A streptococcal (GAS) antigens (M5, M6 and streptodornase B), influenza (the pandemic A/H1N1/California/7/09 NYMC X‐179A and A/H1N1/California/7/09 NYMC X‐181 vaccine antigens, previous Flu‐A and ‐B vaccine targets, A/H1N1/Brisbane/59/2007, A/H1N1/Solomon Islands/3/2006, A/H3N2/Uruguay/716/2007, A/H3N2/Wisconsin/67/2005, A/H5N1/Vietnam/1203/2004 and B/Malaysia/2506/2004), noninfluenza viral targets (CMVpp65, EBNA‐1 and EBNA‐3) and auto‐antigens (hypocretin peptide, Tribbles homolog 2 peptide cocktail and extract from rat hypothalamus tissue). Results IFN‐γ production was significantly increased in whole blood from narcolepsy cases in response to streptococcus serotype M6 (P = 0.0065) and streptodornase B protein (P = 0.0050). T‐cell recognition of M6 and streptodornase B was confirmed at the single‐cell level by intracellular cytokine (IL‐2, IFNγ, tumour necrosis factor‐alpha and IL‐17) production after stimulation with synthetic M6 or streptodornase B peptides. Significantly, higher (P = 0.02) titres of serum antistreptolysin O were observed in narcolepsy cases, compared to vaccinated controls. Conclusion β‐haemolytic GAS may be involved in triggering autoimmune responses in patients who developed narcolepsy symptoms after vaccination with Pandemrix in Sweden, characterized by a Streptococcus pyogenes M‐type‐specific IFN‐γ cellular immune response.